The relationship between Johor Darul Ta’zim Football Club (JDT) brand trust on fans loyalty / Nurul Ain Iftah Suhaimi and Mohammad Adzly Rajli - Suhaimi, Nurul Ain Iftah; Rajli, Mohammad Adzly (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the relationship between Johor Darul Ta'zim (JDT) brand trust and fans' loyalty, addressing gaps in understanding how trust influences loyalty [1]. By identifying key factors shaping brand trust and examining their impact using quantitative metrics, the research contributes valuable insights into sports branding. Findings aim to enhance strategies for fostering stronger fan loyalty and enriching fan experiences during live games. This study employed quantitative research using self-administered questionnaires distributed to 409 randomly selected Johor Darul Ta’zim (JDT) fans during the tournament season. Data were analyzed using inferential statistics, specifically Pearson Correlation Coefficient, to examine the relationship between JDT brand trust and fan loyalty. Convenience sampling ensured accessibility to respondents, representing a subset of the 3,000 official JDT supporters.